2015
DOI: 10.31254/jmr.2015.1207
|View full text |Cite
|
Sign up to set email alerts
|

Pre anaesthetic medication in children: A comparison of intranasal dexmedetomidine versus intranasal midazolam

Abstract: Background & objectives: Children are more anxious and fearful due to their limited cognitive capabilities, lack of understanding of health care system and lack of self control. It becomes an important concern for an anaesthesiologist to relieve their pre-operative anxiety. Midazolam is frequently used as premedication agent in children. New drugs such as the alpha-2 agonists have also been introduced as alternatives for premedication in pediatric patients. The present study was planned to compare intranas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The included studies were published from 2011 to 2022, and a total of 1,495 eligible pediatric patients (ages ranged from 1 month to 14 years) were involved in present analysis. The primary outcomes “number of patients with satisfactory separation from parents, number of patients with satisfactory induction or mask acceptance, and patient’s level of sedation” were reported in 17 studies [ 14 21 , 23 26 , 28 – 30 , 32 , 33 ]. And most of studies paid attention on evaluation in midazolam versus dexmedetomidine, only one study focused on comparison between midazolam and clonidine [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published from 2011 to 2022, and a total of 1,495 eligible pediatric patients (ages ranged from 1 month to 14 years) were involved in present analysis. The primary outcomes “number of patients with satisfactory separation from parents, number of patients with satisfactory induction or mask acceptance, and patient’s level of sedation” were reported in 17 studies [ 14 21 , 23 26 , 28 – 30 , 32 , 33 ]. And most of studies paid attention on evaluation in midazolam versus dexmedetomidine, only one study focused on comparison between midazolam and clonidine [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Singla et al (7) showed that the Modified Objective Pain Scale was significantly less at 30 min after intranasal dexmedetomidine. Midazolam produces sedation by stimulating GABA receptors in the cerebral cortex that inhibits normal neuronal function (8) .…”
Section: Table (6)mentioning
confidence: 99%
“…The intranasal route is convenient and relatively less invasive, avoids the rst-pass hepatic metabolism, and evokes rapid action at the central nervous system [9]. O abel intranasal administration of dexmedetomidine injection in children as drops by springe or as sprays by mucosal atomization device has been widely reported, where the satisfactory sedation with acceptable safety was observed [10][11][12].…”
Section: Introductionmentioning
confidence: 99%